CAD/CAM System for Insole Production - Toma Udiljak; Karlo Obrovac; Igor Ištef (Communications - Scientific letters of the University of Zilina, 2000)
Impressive strides in medicine enhanced a necessity for highly advanced computer systems which would provide measurement and visualization aids with a high degree of accuracy, and high standards for planning and application of specific medical procedures. Orthopaedy, as amedical branch, was enriched for anew approach in design and application of orthoses and prostheses, CAD/CAM. This paper gives an overview about biomechanical characteristics of the foot, which directly implies the features of the future insole. Because of the unity of each foot, the principle of universality, i.e. mass production of insoles, does not give the expected results. Therefore, the advantage is given to production of insoles according to the clinical and pedobarographic finding of the individual. The paper presents the phases in production of insoles by applying CAD/CAM. It describes the developed CAD/CAM system, enabling efficient interfacing of all production phases. The system is developed by applying Open GL, Visual C++ and Visual Basic. It consists of five modules: data base, module for processing and presentation of measured data, module for presentation of the foot RTG pictures, module for modification and adjustments of standardized insoles, and postprocessor.